A REVIEW OF THE MEDICINAL PLANTS IN BULGARIA – COLLECTION, STORAGE, AND EXTRACTION TECHNIQUES - A, Popova; D, Mihaylova (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: As old as humankind itself, plants have been used as a source of flavor, food preservatives, natural remedies, and ailments. As a part of human culture, medicinal plants are recognized for their healing properties, and the plant knowledge has successfully been transferred from generations to present days. Since natural ingredients enhance safety, medicinal plants' significance is constantly gaining interest because of the therapeutic phytochemicals that they contain. Methods and Results: The paper offers summarized information about the collection, storage, and extraction practices used in Bulgaria. A brief information regarding the distribution of the medicinal plants of the Bulgarian dendroflora is provided along with a review of the biological activities possessed. The various applications in the traditional and folk medicine are presented. Conclusion: Sustainable usage of medicinal plants plays a crucial to their conservation and increased healing potency. Thus, this paper reviews and emphasizes on the optimal collection, harvesting, and extracting approaches of medicinal plants